SYSTEM AND CONSISTENCY IN APPLYING QUALIFYING ELEMENTS OF AN OFFENCE - Kondratyuk, S.V; Rumyantsev, P.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
Modern criminal law doctrine as one of the most important principles highlights the differentiation of criminal responsibility for the committed crime. The means of differentiation are quite diverse. These include the legislative distinction of crimes by degree of severity, the establishment of circumstances mitigating or aggravating punishment, grounds for exemption from criminal liability, privileging and qualifying essential elements of an offence, and other means. Unlike other means of differentiation, the assignment to them of qualifying elements of an offence is recognized by most researchers. However, the absence of a legal definition of qualifying elements of an offence, a lack of understanding of their nature at the legislative level by legislator, law enforcers and representatives of the scientific environment leads to errors in the design of legal norms containing qualifying elements and their ambiguous interpretation. In this article, the authors attempt to present the qualifying elements of an offence as a system, to determine its characteristic features and to establish a systematic approach in the use of elements qualifying an offence, with their legislative regulation. This allows to make a number of recommendations to ensure a high level of systematic use of elements qualifying an offence.